Interlocking Narratives: Reconnoitering the Bond and Intersection of Africana women and Africa in Haile Gerima films. - Tigist Alemayehu Gion; Aboneh Ashagrie Zeiyesus; Samuel Tefera Alemu (مجلة الدراسات الاجتماعية)
This article examines the bond and intersection between Africana women residing outside of the continent and Africa, as portrayed in the films of Haile Gerima. Employing qualitative analysis, it scrutinizes the narrative and thematic elements from his works Child of Resistance (1972), Bush Mama (1976), Ashes and Embers (1982), and Sankofa (1993). The focus of the analysis rests on the shared history and memory between Africana women and their African roots, using insights from the Africana womanist theoretical viewpoint. Africana Womanism emphasizes the special experiences and challenges faced by women of African descent. It also stresses the importance of male alliance with women to fight gender inequality and create a fair society. Identifying Gerima as a male filmmaker who is concerned with Africana women’s cinematic representation, the study of his films reveals links between African heritage and the complex issues of race, class, and gender related to their historical reality. Historical and social themes of slavery, anti-colonial struggles, and African culture connect these realities. He also uses the films to create stories that connect the burdens of past injustices with the strength and activism of Africana women today. Through this lens, Gerima’s works emerge as a vital male contribution to the discourse surrounding Africana women.